Tinjauan Kritis terhadap Teori Komunikasi Interpersonal: Implikasi terhadap Hubungan Sosial dalam Era Digital - Kartini, Kartini; Arlintang, Dwi; Fathurrahman, Fathurrahman; Setiawan, Ezzlan Bayu; Al-Farabi, Bayu Febrian; Galib, Alwan; Ainina, Nazma (VISA: Journal of Vision and Ideas, 2024)
Understanding digital literacy was also raised as an important aspect to close the knowledge gap in society regarding the psychological, social and human impacts of digital interactions. And this research contributes to our understanding of how interpersonal communication theory can develop and adapt in the face of continually changing social dynamics, especially in the digital era. In this research, the research method chosen is the library method. This means that the research is focused on reviewing and analyzing literature relevant to the research topic, namely a critical review of interpersonal communication theory and its implications for social relationships in the digital era. This research results in this critical review confirming that interpersonal communication theory remains relevant in the digital era, but must undergo adjustments to be able to face the reality of continuously developing social relationships. Discussion of the implications of this theory becomes the basis for designing new concepts and more effective communication strategies in a dynamic digital environment.